Feeding Effect of the Addition of Linoleic Acid on Meat Quality of Chickens - Simona Kunová; Juraj Čuboň; Andrea Bebejová; Miroslava Kačániová; Peter Haščík; Lukáš Hleba; Jana Tkáčová; Klára Vavrišinová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The aim of this study was to analyse the influence of linoleic acid which was added in the broiler chickens feed mixtures in relation to chemical composition of meat, content of fatty acids and composition of blood serum. There were compared the characteristics of two groups of ROSS 308 chickens in the experiment (the experimental group with 5% addition of linoleic acid and the control group). The protein content of breast was significantly lower (P ≤ 0.05) in the experimental group than in the control group. There were found significant differences (P ≤ 0.05) in the protein content between sexes. There was found statistically significant (P ≤ 0.01) higher fat content in the breast of experimental group in comparison with control group. Statistically significant differences (P ≤ 0.05) were found in fat from the thigh meat of experimental group than the control group. The analysis of the chemical composition showed higher content of fat in the breast (1.9 g.100 g−1) than in the thigh (11.66 g.100 g−1) of chickens which were fed with the addition of linoleic acid to feed mixture. This resulted in lower share of the other components. The addition of linoleic acid in the chickens feed mixture showed significantly higher proportion of polyunsaturated fatty acids to saturated fatty acids (0.76). Analysis of blood serum showed higher concentration of chlorides (P ≤ 0.01) in the group with the addition of linoleic acid than the control group. Proportion of monounsaturated fatty acids was 47.06% in the experimental group and significantly higher one (53.77%) was found in the control group.